If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2 = 12 + -66 Reorder the terms: -2 + 4x = 12 + -66 Combine like terms: 12 + -66 = -54 -2 + 4x = -54 Solving -2 + 4x = -54 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4x = -54 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = -54 + 2 4x = -54 + 2 Combine like terms: -54 + 2 = -52 4x = -52 Divide each side by '4'. x = -13 Simplifying x = -13
| 6a^2-2ax=0 | | 6x^2-2ax=0 | | 40+0.25m=80 | | 0=-3x^2-6x+4 | | lx^2-kx+8=0 | | x^2-kx-24=0 | | -2n+4=12 | | x^2-4kx+(5k-6)=0 | | 7y^2(y-2)=0 | | f(x)=8/3x^4 | | -x+7-6x=19-3y | | X^2+2y=10 | | 2u^2+3u=0 | | 4a+14b=92 | | 4a+4b=32 | | 1.2X=0.12 | | 27+x=6 | | 6a+11b=102 | | 6a+4b=60 | | -5c(9c-8c-5)= | | -7/8-8-1/7= | | 6u+v=46 | | -7/8*-8*-1/7= | | 0=-16xt^2+40xt+7 | | 3u+v=28 | | 3s+7t=80 | | (((-7)/8)*(-8)*(-1))/7= | | 10s+7t=136 | | 8m+4n=108 | | (((-7)/8)(-8)(-1))/7= | | 8m+7n=123 | | 7W+3+104=w |